Single-cell transcriptomic analysis identifies a stress response Schwann cell subtype - Lan Xianfeng; Zheng Yanmei; You Yongliang; Wu Xuejun; Wu Shaojie; Chen Nengfu; Wang Lihong; Yang Wenfu (Open Medicine)
Peripheral nerve injury can lead to sensory, motor, and autonomic nerve dysfunction, significantly impacting patients’ quality of life. Schwann cells (SCs), as key components of the peripheral nervous system, play a crucial role in nerve repair. However, many functionally specialized and flexible SC subtypes remain unidentified. Recent advancements in single-cell transcriptomics have enabled a deeper understanding of SC heterogeneity during peripheral nervous system development.